Implementing the pedagogical potential of social and cultural activities in the institutional environment - Vladlenovich Kamenets, Aleksandr (2021)
The article is concerned with the further development of social and cultural activities due to their great social demand. The authors of the article associate this task with the influence of social institutions on state cultural organizations providing leisure activities for different groups of the population. They have considered the specifics of such impacts in the Russian society of the transition period. As a result, they have revealed new opportunities in forming programs of social and cultural activities with the use of their creative achievements throughout the history of Russia and foreign countries. In addition, the article traces the most common trends in socio-cultural activities focused on institutional and state issues and determines the most promising forms of such activities. In this process, a significant role is played by socio-cultural clubs and mass theater programs. The article sets new priorities in the further development of amateur activities and performances, which effectively combines mass participation and skillfulness. The study also outlines prospects for a more active state participation in the organization of social and cultural activities.